HuPho: the human phosphatase portal. (24th August 2012) - Liberti, Susanna; Sacco, Francesca; Calderone, Alberto; Perfetto, Livia; Iannuccelli, Marta; Panni, Simona; Santonico, Elena; Palma, Anita; Nardozza, Aurelio P.; Castagnoli, Luisa; Cesareni, Gianni
<x xml:space="preserve">Abstract</x> Phosphatases and kinases contribute to the regulation of protein phosphorylation homeostasis in the cell. Phosphorylation is a key post‐translational modification underlying the regulation of many cellular processes. Thus, a comprehensive picture of phosphatase function and the identification of their target substrates would aid a systematic approach to a mechanistic description of cell signalling. Here we present a website designed to facilitate the retrieval of information about human protein phosphatases. To this end we developed a search engine to recover and integrate information annotated in several publicly available web resources. In addition we present a text‐mining‐assisted annotation effort aimed at extracting phosphatase related data reported in the scientific literature. The HuPho (human phosphatases) website can be accessed at http://hupho.uniroma2.it.